Application of C-N fractal model, factor analysis, and geochemical mineralization probability index (GMPI) for delineating geochemical anomalies related to Mn-Fe deposit and associated Cu mineralization in west-central Sinai, Egypt. Issue 3 (2021) - Helba, Hossam A.; , Ahmed M. El-Makky; Khalil, Khalil I.
No abstract available